TECHNOLOGICAL SOLUTIONS AIMING AT RECOVERING METRO BRAKING ENERGY: A MULTI-CRITERIA ANALYSIS CASE STUDY - Bernardini, Annalia; Barrero, Ricardo; Macharis, Cathy; Van Mierlo, Joeri (BDC. Bollettino Del Centro Calza Bini, 2014)
The transport sector, being responsible for a large share of fossil fuels consumption and emissions, mainly CO2, is seeking for different ways of reducing their energy consumption and, especially, their dependency on fossil fuels. The purpose of this paper is to present the Multi-Criteria Analysis (MCA) of technological solutions recovering metro braking energy. The MCA PROMETHEE method endorsed to select the most suitable technological solution for the tram and metro network in Brussels. The MCA approach allowed to firstly evaluate the different technologies and afterwards to propose an individual decision to the public transport decision-maker based on the decision problem objectives and the MCA results. Keywords: public transport, metro braking energy, PROMETHEE